PENGARUH PROMOSI, HARGA, MARKETING DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI PADA PT. PLANET BAN CABANG KOTA BANGKALAN - Salsa Bila; Manah Tarman; Aulia Dawam (JURNAL ILMIAH EDUNOMIKA, 2023)
Planet Ban continues to move more competitively with the increasing number of competitors which encourages Planet Ban to innovate more. One of the efforts made is to invite potential customers to visit the Planet Ban store. PT. Planet Ban implements the concept of Customer Relationship Marketing (CMR), which aims to increase long-term growth in company profitability. This research uses a case study on Planet Tire consumers with the position of PT. As Planet Ban continues to grow, it will certainly maintain its loyalty and relationship with customers. The purpose of this study is to examine the factors that can affect consumer loyalty to Planet Ban Branch, Bangkalan City by taking the theme "The Influence of Promotion, Price, Marketing and Quality of Service on Consumer Loyalty with Consumer Satisfaction as a Mediation Variable (Case Study on PT. Planet Ban Consumers in Bangalore city branch). The results of this study indicate an R square value of 0.918 which means that Promotion, Price, Marketing and Service Quality have an influence of 91.8% on Consumer Satisfaction through Consumer Loyalty. In the output of the first model regression in table 3 it is said that the four variables have no significant effect. The results conclude that Promotion, Price, Marketing and Service Quality have no significant effect on Consumer Loyalty. At the output of the second regression model in table 4 it is said that two variables namely Promotion and Service Quality have a significant effect on Customer Satisfaction while Price and Marketing have no significant effect on Customer Satisfaction. The results of the analysis of the partial T test on H1 show that the calculated t value is greater than the t table value. So that the Ho hypothesis is rejected and accepts the H1 hypothesis where promotion, price, marketing and service quality affect consumer satisfaction. The results of the analysis of the partial T test on H2 show that the calculated t value is greater than the t table value. So that the hypothesis Ho is rejected and accepts the hypothesis H2 that promotion, price, marketing and service quality affect consumer loyalty. The results of the partial T test analysis on H3 show that t count is greater than t table. So it can be concluded that Ho is rejected and accepts H3 that customer satisfaction affects consumer loyalty. The results of the analysis of the simultaneous F test that it is known that the calculated F value is greater than the table F value so that it can be concluded to reject Ho and accept H4 that simultaneously the independent variable has a positive effect on the dependent through the intervening variable.